2014
DOI: 10.1016/j.thromres.2013.10.015
|View full text |Cite
|
Sign up to set email alerts
|

Long-term efficacy and safety of a pasteurized, plasma-derived factor VIII concentrate (Beriate® P) in patients with haemophilia A

Abstract: Beriate(®) P has an excellent efficacy and safety profile. Many patients who were initiated on Beriate(®) P at our centre remain on the treatment today.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 28 publications
1
5
0
Order By: Relevance
“…In summary, our findings from the MAPPs-analyses performed herein demonstrate its utility for identifying and characterizing the molecular-determinants of FVIII-immunogenicity. Consistent-with our Gate-Keeper-hypothesis, we have shown that significant HLAcII/FVIII-peptidome-level differences likely mediate the distinct risks of inhibitor-development observed clinically for various FVIIIs including: 1) pdFVIIIs vs.-rFVIIIs; 2) non-engineered-vs.-engineered-rFVIIIs; and-3) next-generation-vs.-original-FDA-approved-rFVIIIs [34][35][36][37][38][39]75]. We showed that pre-incubation of FVIIIs with pdVWF significantly-decreases their HLAcIIbound/FVIII-derived-peptide counts, and that this protective-effect is differentially-manifested across rFVIIIs.…”
Section: Author Manuscriptsupporting
confidence: 83%
See 3 more Smart Citations
“…In summary, our findings from the MAPPs-analyses performed herein demonstrate its utility for identifying and characterizing the molecular-determinants of FVIII-immunogenicity. Consistent-with our Gate-Keeper-hypothesis, we have shown that significant HLAcII/FVIII-peptidome-level differences likely mediate the distinct risks of inhibitor-development observed clinically for various FVIIIs including: 1) pdFVIIIs vs.-rFVIIIs; 2) non-engineered-vs.-engineered-rFVIIIs; and-3) next-generation-vs.-original-FDA-approved-rFVIIIs [34][35][36][37][38][39]75]. We showed that pre-incubation of FVIIIs with pdVWF significantly-decreases their HLAcIIbound/FVIII-derived-peptide counts, and that this protective-effect is differentially-manifested across rFVIIIs.…”
Section: Author Manuscriptsupporting
confidence: 83%
“…The pdFVIII studied originated as Beriate ® (CSL Behring GmbH), which contains pdVWF (Figure S1) at concentrations varying lot to lot . As described previously, pdVWF in the combined reconstituted Beriate was first removed and the VWF‐free pdFVIII (Figure ) was DC‐PPPA‐tested as pdFVIII + pdVWF after add‐back of pdVWF at 13.4‐molar‐excess using a FVIII‐free pdVWF concentrate (see Formulations of FVIIIs) .…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Well-known examples of the latter are chikungunya 70 and dengue virus, 71 but many other viruses, often without a disease caused by the virus, have been repeatedly mentioned in this respect. [72][73][74] Due to the nature of the methods in use for plasma products, like pasteurization, 75 solvent-detergent treatment, 70 freeze-drying 76 and nanofiltration, 77,78 these methods cannot be applied to cellular products.…”
Section: Remaining Risk After Introduction Of Screeningmentioning
confidence: 99%